Literature, Discourse and Ideology: Dialogizing Edgar Allan Poe’s “The Fall of The House of Usher” in Terms of the Languages of Sexism, Classism and Racism - Jiménez Rodríguez, Adriana (2013)
The article analyzes Edgar Allan Poe’s famous short story “The Fall of the House of Usher” through the perspective of Mikhail Bakhtin’s theories regarding literature and language. Bakhtin proposes that the novel in particular is an ideal medium that serves to study the interplay of many languages and ideologies. Taking that as a premise, the approach in the present discussion is historical-social, as it strives to trace three particular discourses in the short story: sexism, classism, and racism. The specific objective of the article is to prove that the dialogization of those discourses seeks, in a way, to point out the social and historical necessity to escape such oppressive systems.